Individual Author’s Adjective-Neologisms with Floral Semantic Elements in the Ukrainian Poetry of the XX-XXI-th Century (Linguostylistic Studies, 2016)
The article considers semantic structure of the authors’ adjective-neologisms/occasionalisms in the poetic texts of the Ukrainian poetry in 20-21st century. The emphasis is laid on the floral lexemes of these neologisms: names of flowers (asters, poppies, mint, tarragon, violet and others), dendronyms (lilac, cherry, cranberry, poplar, birch, etc.), phytocenoses (forest, steppe). In the focus of attention are the floral symbols, their sacramental nature consecrated by the folk tradition and typical for the Ukrainian ethnospace. The author argues that the adjectival neologisms, the semantic structure of which involves phyto-symbols in the poetic language, are often created to convey such key concepts of the Ukrainian culture as Ukraine, freedom, beauty, love, sadness, joy. Being raditional for folk art, they acquire new individual author meanings in the poetic texts. Key words: individual-authorial adjectives, component, florolexeme, neologisms, semantics, symbol, Ukrainian poetry of the XX–XXI centuries.             References